Analysis of Ferdinand De Sausure Semiotics on John Doe Character in The Se7en Movie - faizar yuliansyah; nuning indah pratiwi (Universitas Bunda Mulia, 2023)
These days movies as a mass media product that people likes, has the unique characteristics provide information or even deliver messages to the audiences in the form of entertainment. Besides that the film has a lot of advantages also that makes it the best entertainment provider to the audiences. Such as visualized an idea so that people can understand the ideas, real messages and make it even better or interesting than the actual events. Besides that, we are as a human have limited space and time to knowing all the things that happened in our world. From movies we can understand many things; science, history, information, etc. movies can also make us emotional and arouse interest, that because were as a audience feels like in the movies thinking and behave like the main character from the movies. Such as Se7en, Se7en is one of the Hollywood fenomenal movies. This movies is the subject of this research, study the main antagonist character, John Doe, using Ferdinand De Sausure semiotics theory which the analysis formed above Signifier & Signified, Langue-Parole, Syntagmatic- Paradigmatic, Synchrony and Diachrony using qualitative methods inside the observation and deep interviews technique about the dialogue and the scene inside the movies with the informant expert and communication student who understand the semiotics theory and movies. This research found that John Doe Character is very mysterious, idealist but smart and intelligent, ruthless. It was obtained from theÂ observation from scenes, dialogues, words, signs that are attached to the characters John Doe and the other element that supportsÂ the research from the movie Se7en.Keywords : Semiotics, Movies, Character, Se7en